2008
DOI: 10.1002/jobm.200700289
|View full text |Cite
|
Sign up to set email alerts
|

Detection by PCR of adhesins genes and slime production in clinical Staphylococcus aureus

Abstract: The presence of the ica loci and adhesins genes in clinical Staphylococcus aureus strains were considered important factors of virulence. In this study, 46 strains of Staphylococcus aureus were isolated from auricular infection, and were investigated for slime production using Congo Red Agar method (CRA). In order to detect the adhesins genes (ica A, ica D, fnb A, cna, Clf A) Polymerase Chain Reaction was used. Qualitative biofilm production of S. aureus using CRA plates revealed that 56.5% of strains were sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
(59 reference statements)
2
19
1
1
Order By: Relevance
“…They detected fnbAin all strains while the rate of fnbBwas 99%, 43%, and 0% in the 3 clones, respectively. In another study focusing on strains isolated from soft tissue infections, the rate of fnbAwas reported as 76.1% (Zmantar et al, 2008). These literature survey supports that as per the aim of the present study, the genes encoding the virulence factors play a role in the pathogeneses of community acquired musculoskeletal and skin/soft tissue infections.…”
Section: Antibacterial Activity Of Herbal-silver Nanocomposite Hs Nc supporting
confidence: 87%
“…They detected fnbAin all strains while the rate of fnbBwas 99%, 43%, and 0% in the 3 clones, respectively. In another study focusing on strains isolated from soft tissue infections, the rate of fnbAwas reported as 76.1% (Zmantar et al, 2008). These literature survey supports that as per the aim of the present study, the genes encoding the virulence factors play a role in the pathogeneses of community acquired musculoskeletal and skin/soft tissue infections.…”
Section: Antibacterial Activity Of Herbal-silver Nanocomposite Hs Nc supporting
confidence: 87%
“…Qualitative detection of slime formation was studied by culturing the isolated strains on Congo red agar plate (CRA) as previously described (Chaieb et al 2007;Zmantar et al 2008). After incubation, black colonies were considered as slime positive, whereas slime-negative strains formed pinkish red, smooth colonies with a darkening at the center.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Structurally, both PIA and PS/A are similar with a common backbone of β-1-6-linked polyglucosamine, but differ in the primary substitutions in their amino groups. The intercellular adhesion (ica) locus consisting of the genes icaADB and C encodes the proteins mediating the synthesis of PIA and PS/A in staphylococcal species (Cramton et al 1999;Zmantar et al 2008). Among the ica genes, icaA and icaD have been reported to a play a significant role in biofilm formation in S. aureus.…”
Section: Introductionmentioning
confidence: 99%